2012
DOI: 10.1530/joe-12-0286
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Ca2+-responsive transactivator in high glucose-induced β-cell apoptosis

Abstract: The calcium-regulated transcription coactivator, Ca 2C -responsive transactivator (CREST) was expressed in pancreatic b-cells. Moreover, CREST expression became significantly increased in pancreatic islets isolated from hyperglycemic Goto-Kakizaki rats compared with normoglycemic Wistar controls. In addition, culture of b-cells in the presence of high glucose concentrations also increased CREST expression in vitro. To further investigate the role of this transactivator in the regulation of b-cell function, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous study with Northern blot and in situ hybridization analysis has indicated that CREST mRNA is widely expressed in various peripheral organs and tissues including the testis (Aizawa et al 2004); whereas, the expression of CREST at the protein level has only been detected in the brain and pancreas with Western blot and /or immunohistochemistry (Aizawa et al 2004;Men et al 2013). In the present study, we demonstrated for the first time CREST protein expression in the rat and human testis with immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study with Northern blot and in situ hybridization analysis has indicated that CREST mRNA is widely expressed in various peripheral organs and tissues including the testis (Aizawa et al 2004); whereas, the expression of CREST at the protein level has only been detected in the brain and pancreas with Western blot and /or immunohistochemistry (Aizawa et al 2004;Men et al 2013). In the present study, we demonstrated for the first time CREST protein expression in the rat and human testis with immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expression in the nervous system, CREST mRNA can also be detected in the peripheral organs of the rats, such as the heart, liver, kidney, pancreas and testis (Aizawa et al 2004;Men et al 2013). Direct relation of the increase in expression of CREST in pancreatic β-cells of hyperglycemic rats to high glucose-induced apoptosis suggests multifunction of CREST in non-nervous tissues (Men et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation